Tool or hassle?- Production workers evaluation of the potential of digital assistance systems on the shopfloor in shipbuilding projects. Issue 1 (31st December 2023) - Giskeødegård, Marte; Kjersem, Kristina; Jahn, Niklas; Rost, Robert
Abstract: Technology development opens up for new possibilities to facilitate the production processes through digital information systems. To optimize the systems' value, the form, content, and medium must fit the needs of the workers. This article aims to contribute to the discussion on value, use and design of digital assistance systems for production. It presents empirical data from a case study at a Norwegian shipyard, on production workers' perception of coordinative challenges, and the value (including content) of digital assistance systems in complex shipbuilding projects. A quantitative survey among supervisors and operators at the shop floor was conducted twice due to different circumstances at the yard. These variations in circumstances are valuable to enable an evaluation of the workers' perception of coordinative challenges and digital solutions in different situations. The findings indicate a pronounced positive attitude towards the potential of digital systems. Moreover, the role of supervisors and operators in coordinative challenges leads to different requirements to the solutions. The results from this study will have both industrial and scientific implications, as they provide valuable insights to help develop user-friendly systems that aid both workers and the company in terms of efficiency and accurate communication.